Transcutaneous electrical acupoint stimulation combined with electroacupuncture promotes rapid recovery after abdominal surgery: Study protocol for a randomized controlled trial - Li, Hao; Du, Chen; Lu, Lingyun; Hu, Xiangyun; Xu, Huiming; Li, Ning; Liu, Hong; Wen, Qian (Frontiers in Public Health, 2022)
Background After abdominal surgery, the most common complications include decreased appetite or loss of appetite, abdominal distension, abdominal pain caused by declined or disappeared gastrointestinal motility, anal arrest with intestinal distension and defecation, and nausea and vomiting caused by the use of anesthetics and opioid analgesics. These complications seriously affect postoperative recovery, prolong hospital stay, and increase the patient burden. This study investigated the efficacy and safety of three acupoint stimulation modalities (electroacupuncture, EA, transcutaneous electrical acupoint stimulation, TEAS; transcutaneous acupoint electrical stimulation combined with electroacupuncture, TEAS+EA) and two electroacupuncture instrument waveforms (continuous wave and dilatational wave) for rapid recovery after abdominal surgery. Methods A total of 560 patients will be recruited and randomly divided into seven groups: Continuous Wave Electroacupuncture Group (cEA), Continuous Wave Transcutaneous Electrical Acupoint Stimulation Group (cTEAS), Continuous Wave Transcutaneous Electrical Acupoint Stimulation combined with Electroacupuncture Group (cTEAS+EA), Dilatational Wave Electroacupuncture Group (dEA), Dilatational Wave Transcutaneous Electrical Acupoint Stimulation Group (dTEAS), Dilatational Wave Transcutaneous Electrical Acupoint Stimulation combined with Electroacupuncture Group (dTEAS+EA), and Control Group. Continuous waves were selected at 2 Hz, and dilatational waves were selected at 2/50 Hz. EA stimulated bilateral Neiguan (PC6), Hegu (LI6), Zusanli (ST36), Shangjuxu (ST37), and Xiajuxu (ST39). TEAS stimulation of bilateral Liangmen (ST21) and Daheng (SP15). The control group did not receive any electroacupuncture or transcutaneous electrical acupoint stimulation. All patients received ERAS standardized perioperative management. Treatment started on the first postoperative day, once daily in the morning, until the patient regained spontaneous bowel movements and could tolerate transoral solid food. The primary outcome was GI-2, a composite of time to first defecation and time to tolerance to a solid diet. Secondary outcomes will include time to first exhaustion, time to first defecation, time to tolerance to a solid diet, time to first ambulation, length of hospital stay from surgery to discharge, postoperative daily pain and nausea and vomiting Visual Analog Scale (VAS) score, incidence of postoperative complications, and assessment of treatment acceptability. Discussion This study will compare the efficacy and safety of three acupoint stimulation methods and two electroacupuncture instrument waveforms in rapid recovery after abdominal surgery.